Strategic psychotherapy and the "decagonal model" in clinical practice - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
Starting from the strategic model, this research focuses on its critical aspects, to suggest a dynamic and structured model, called "decagonal model" to be applied in clinical practice and organised by actions (what), purpose (why), time/place (when/where) and modality (how). Framing the patient's symptomatology in a specific nosographic framework (structural component) is therefore useful to take a picture of him and to recognise the habitual toxic patterns and tendencies of his personality, but the strategic operations to be put in place are to place the emphasis on the functional aspect of his personality (functional component), working on his resources, on the solutions attempted, on the vicious circles reproduced, on emotional literacy and awareness.